Overview of the Liulin type instruments for space radiation measurement and their scientific results. (January 2015) - Dachev, T.P.; Semkova, J.V.; Tomov, B.T.; Matviichuk, Yu.N.; Dimitrov, P.G.; Koleva, R.T.; Malchev, St.; Bankov, N.G.; Shurshakov, V.A.; Benghin, V.V.; Yarmanova, E.N.; Ivanova, O.A.; et al.
Abstract: Ionizing radiation is recognized to be one of the main health concerns for humans in the space radiation environment. Estimation of space radiation effects on health requires the accurate knowledge of the accumulated absorbed dose, which depends on the global space radiation distribution, solar cycle and local shielding generated by the 3D mass distribution of the space vehicle. This paper presents an overview of the spectrometer–dosimeters of the Liulin type, which were developed in the late 1980s and have been in use since then. Two major measurement systems have been developed by our team. The first one is based on one silicon detector and is known as a Liulin-type deposited energy spectrometer (DES) (Dachev et al., 2002, 2003 ), while the second one is a dosimetric telescope (DT) with two or three silicon detectors. The Liulin-type instruments were calibrated using a number of radioactive sources and particle accelerators. The main results of the calibrations are presented in the paper. In the last section of the paper some of the most significant scientific results obtained in space and on aircraft, balloon and rocket flights since 1989 are presented. Highlights: Different modifications of Liulin type spectrometers are presented. The high scientific values are coming mainly from the extensive calibrations. The data analysis procedure allows characterization of the different radiation sources. The main advantage is their low weight, low power consumption and low cost.